Medical and Legal Evaluation of Sexual Hallucinations Under Anesthesia and Sedation: Case Reports - Mutlu, Emre; Aşıcıoğlu, Faruk (The Bulletin of Legal Medicine, 2019)
Dreaming and hallucinations under sedation or anesthesia have been known since the early stages of anesthesia. Sexual hallucinations that develop under the influence of sedative or hypnotic drugs may lead to allegations of sexual harassment or assault by physicians, nurses and other health professionals who perform the intervention, as they are thought to be real and felt intensely by the patient. In order to prevent the physicians from being the subject of false accusations, it may be advisable that the intervening halls should be under surveillance, without interfering with the ethical sensitivity, if possible with other health workers of the same sex as the patient. The investigation of the drugs in terms of hallucinogenic effect during phase studies prior to the introduction to clinical use is also important to prevent similar cases. On the other hand, it is necessary to take all claims seriously and to investigate whether there ...
Keywords: anesthesia; sexual hallucinations; legal evaluation